2006
DOI: 10.1002/j.2048-7940.2006.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Restraint Reduction in the Acute Rehabilitation Setting

Abstract: A prospective, continuous quality improvement study was implemented at a hospital on two rehabilitation units: stroke and brain injury. The purpose of the study was to decrease restraint use by 25% and to maintain fall rates no greater than 10% over baseline. A multi-component restraint reduction program was implemented that focused on administrative support, education, consultation, and feedback. Monthly restraint rates and fall rates were monitored and compared to the previous year's rates. Both units reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…The reduction in physical restraint use was not shown to increase fall reports on the units. Although information on why restraints were being used was not available, the fact that falls did not increase as physical restraint use decreased is consistent with the literature …”
Section: Discussionmentioning
confidence: 99%
“…The reduction in physical restraint use was not shown to increase fall reports on the units. Although information on why restraints were being used was not available, the fact that falls did not increase as physical restraint use decreased is consistent with the literature …”
Section: Discussionmentioning
confidence: 99%
“…One study was an interrupted time series 24 . The remaining studies used quasi-experimental designs: eight were pretest-posttest 9,13,[25][26][27][28][29][30] , five were non-equivalent groups 15,17,19,20,31 and one was a post-test study 14 . Details of study characteristics are summarised in Table 2.…”
Section: Description Of Eligible Studiesmentioning
confidence: 99%
“…Over half the studies involved the education or training of nurses (57%). All but one study 25 reported the number of patients included in outcome measurements, which totalled 9,913 across 20 studies (median 495, range 37 to 1696).…”
Section: Description Of Eligible Studiesmentioning
confidence: 99%
“…This issue is contradictory to different supervisions and standards related to the reduction or prevention of physical restraint in other health-therapeutic centers (18). Nurses used physical restraint as a part of therapeutic methods in different units for many years (19), but the use of physical restraint technique is a controversial issue (20).…”
Section: Discussionmentioning
confidence: 98%